Analisis Ionic Soil Stabilizer (Iss 2500) Terhadap Nilai Durabilitas Tanah Lempung Plastisitas Rendah Pada Perkerasan Jalan - Amelia Oktavia; Idharmahadi Adha; Setyanto Setyanto (CIVED, 2021)
Various methods of soil stabilizations in Indonesia are more increasingly used for soil quality improvement, one of the methods is using chemically additive materials with ISS 2500 (Ionic Soil Stabilizer). This chemical solution is able to cover soil particles through electro-chemical reactions, so that the water content is separated and cohesion among soil particles is strengthened. However, unstable weather and temperature changes (durability) in forms of rainfall and heat influence and cause soil defects especially in road construction. In this reseach, the tested soil was clay with low plasticity from Karang Anyar region in Lampung Selatan regency, and mixed with 0.9 ml of ISS 2500 solution content the ISS optimum content. To enable reactions between soil and ISS 2500, the mixed soil was treated in 18 days with durability treatment and cycles addition; 0,2,4, and 6 cycles. The laboratory results indicated that CBR test in cycle 0, 2, 4, and 6 obtained 8%, 7.6%, 5.7%, and 5.1% respectively.  The CBR value of the mix decreased regularly along with given amounts of additional cycles. However, the overall CBR value of the stabilization of low plasticity clay with an ISS of 2500 (Ionic Soil Stabilizer) can meet the requirements of Bina Marga as subgrade, because the CBR value obtained is greater than 5% even though it is given cycle treatment. The ISS 2500 material can be used as an alternative stabilization material for the improvement of the subgrade.